Rancang Bangun Sistem Informasi Peran Masyarakat Atasi Karhutla Berbasis Website - Bartheli, Exanio; Geges, Septian (Journal of Information Technology and Computer Science, 2021)
Forest fires are very vulnerable to occur in Indonesia, so they will have a dangerous impact on society and the ecosystem. So it is very important to have knowledge about forest and land fires to prevent things that are harmful to the community. Based on this background, a Website-Based Website-Based Information System for Community Roles Overcome Forest and Land Fires was made. The methodology used in making the website for the role of the community in dealing with forest and land fires is waterfall according to Sommerville (2011:29-30), with stages, namely Requirement Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing and Operation and Maintenance. The programming languages used are HTML, PHP, CSS, Bootstrap, Javascript and MySQL, Integration and System Testing using the Blackbox Method. On this website there are several features, namely, homepage, articles, galleries, contacts, member lists, donations and reporting features via WhatsApp. With the aim that the public can get information about forest and land fires, provide assistance in the form of donations and report in the event of forest or land fires via WhatsApp.